Spectrophotometric determination of glycolic acid with chromotropic acid assisted by microwave oven - Gigante, A. C.; Pezza, L.; Pezza, H. R. (Editora Unesp, 2002)
In this work, a rapid, simple and selective spectrophotometric for the determination of glycolic acid is proposed, This method is based on selective reaction between the formaldehyde splitted off by the glycolic acid, which reacts with chromotropic acid in a phosphoric acid medium, producing a violet-red compound (lambda(max) = 570 nm). The colored compound formation was accelerated by irradiating the reacting mixture with microwave energy for 30 seconds (1.100 W). Beer's Law is obeyed in a concentration range of 0-2,208 mg L-1. The proposed method was applied in the analysis of comercial samples of glycolic acid. Recoveries were within 97% to 101.4%, with standard deviations ranging from 0.2% to 0.4%.
Keywords: glycolic acid; chromotropic acid; spectrophotometry; irradiation by microwave